องค์ประกอบภาวะผู้นำาของผู้บริหารวิทยาลัยพยาบาล สังกัดกระทรวงสาธารณสุข - นพรุจจินดา สุภาวดี; ชินะตังกูร ศิริชัย (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1)ทราบองค์ประกอบภาวะผู้นำของผู้บริหารวิทยาลัยพยาบาลสังกัดกระทรวงสาธารณสุข 2) ยืนยันองค์ประกอบภาวะผู้นำของผู้บริหารวิทยาลัยพยาบาล สังกัดกระทรวงสาธารณสุข ขั้นตอนการวิจัยประกอบด้วย 3 ขั้นตอน คือ 1) ศึกษาวิเคราะห์เพื่อกำหนดกรอบแนวคิดการวิจัย 2) การศึกษาวิเคราะห์องค์ประกอบ 3) การยืนยันองค์ประกอบภาวะผู้นำของผู้บริหารวิทยาลัยพยาบาล สังกัดกระทรวงสาธารณสุข กลุ่มตัวอย่าง ได้แก่ บุคลากรที่ปฏิบัติหน้าที่อาจารย์ในวิทยาลัยพยาบาล สังกัดกระทรวงสาธารณสุข จำนวน 313 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบสัมภาษณ์แบบกึ่งโครงสร้างแบบสอบถาม และแบบตรวจสอบรายการ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าความถี่ (Frequency) ค่าร้อยละ (Percentage) ค่ามัชฉิมเลขคณิต (Mean) ส่วนเบี่ยงเบนมาตรฐาน (Standard Deviation) การวิเคราะห์องค์ประกอบเชิงสำรวจ (Exploratory Factor Analysis) และการวิเคราะห์เนื้อหา (Content Analysis) ผลการวิจัยพบว่า 1. องค์ประกอบภาวะผู้นำของผู้บริหารวิทยาลัยพยาบาล สังกัดกระทรวงสาธารณสุข ประกอบด้วย 7 องค์ประกอบ คือ (1) ผู้นำวิสัยทัศน์ (2) ผู้นำการเปลี่ยนแปลง (3) ผู้นำทางวิชาชีพ (4) ผู้นำจริยธรรม (5) ผู้นำสร้างแรงบันดาลใจ (6) ผู้นำคำนึงถึงความเป็นปัจเจกบุคคล (7) ผู้นำด้านเทคโนโลยี 2. องค์ประกอบภาวะผู้นำของผู้บริหารวิทยาลัยพยาบาล สังกัดกระทรวงสาธารณสุข ที่ประกอบด้วย 7 องค์ประกอบมีความเหมาะสม มีความเป็นไปได้ ถูกต้องและสามารถนำไปใช้ประโยชน์ได้สอดคล้องกับแนวคิดทฤษฎีของการวิจัย LEADERSHIP FACTORS FOR NURSING COLLEGE ADMINISTRATORS THE JURISDICTION OF THE MINISTRY OF PUBLIC HEALTH The purposes of this research were to 1) identify the components of leadership factors for nursing college administrators under the jurisdiction of the Ministry of Public Health and 2) confirm leadership factors of nursing college administrators, Ministry of Public Health. The research procedures consisted of 3 steps: 1) study and analyze conceptual framework 2) study and analyze the factors 3) confirm leadership factors for nursing college administrators, Ministry of Public Health. The samples consisted of 313 nursing instructors in college of nursing under the jurisdiction of the Ministry of Public Health. The research instruments were semistructured interviews, questionnaires and checklists form. The statistics to analyze the data were frequencies, percentage, Mean, Standard Deviation, exploratory factor analysis and content analysis. The research findings were as follows: 1. The component of leadership of nursing college administrators under the jurisdiction of the Ministry of Public Health consisted of 7 components which were: 1) Visionary Leadership 2) Change Leadership 3) Professional Leadership 4) Ethical Leadesship 5) Inspirational Leadership 6) Individualized Consideration Leadership 7) Technological Leadership. 2. The 7 leadership factors for Nursing College Administrators under the Jurisdiction of the Ministry of Public Health are appropriated, feasible, accurate and applicable which coincided with the research theory.